SEKSUALITAS DAN RELASI LAKI-LAKI PEREMPUAN DALAM SAJAK "PERSETUBUHAN KUNTHI" KARYA GOENAWAN MOHAMAD - Banita, Baban; Rahayu, Lina Meilinawati; Adipurwawidjana, Ari J. (Diksi, 2020)
(Title: Sexuality and Relation Man’s and Woman’s in the Poem "Persetubuhan Bumi" by Goenawan Mohamad). Inequality between woman and man in asexual relationship appear many time in Indonesia’s poetry. Women are often being put in a second position even though they have the same competence and power with men. It also happens in relationship on daily activities, both at public space or at home. Women are often connected to a domestic work and have to do many things as away to prove her devotion to men. This affected even to the most private relation between men and women. Women often positioned as a tool to satisfy men’s sexual desire. In Goenawan Mohamad’s poems, he displays sexuality and relation between men and women in a unique and beautiful way. In this relationship, women are still put in second position, althought the woman genuinely enjoy and satisfied from the sexual activity. Women are shown as a passive body in the hand of men’s power. This research is using theory of intertextual and gender. This research shows that there are many factors that created inequality between men and women in a subject of sexual relationship. Keywords: sexuality, relation, intertextual, feminist.